2014
DOI: 10.4081/ija.2014.602
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus cruentus L. is suitable for cultivation in Central Italy: field evaluation and response to plant densities

Abstract: The aim of this study was to determine the possibility of amaranth cultivation in Central Italy and to determine the optimum plant density. Field trials were carried out in 2011 and 2012 under non-irrigated conditions in Tuscany (43° 18' N, 11° 47' E). Twelve accessions of two amaranth species (Amaranthus cruentus L. and A. hypochondriacus L.) were utilised. Genotypes were evaluated over a two-year period using a RCB design with three replicates. The effects of plant density were investigated in 2012. A with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
4
12
3
3
Order By: Relevance
“…On the other hand, it is known that the grain yield strongly varies depending, not only on genotype, but also on site, pedo-climatic conditions, growing season and agronomic practices (Gimplinger et al, 2008;Rivelli et al, 2008). However, the genotypes here investigated, exhibited good potential levels of grain yield in both soil types, reaching values consistent with those reported in literature (Myers, 1996;Kaul et al, 2000;Pospiŝil et al, 2006;Gimplinger et al, 2008;Rivelli et al, 2008;Casini and La Rocca, 2014), even if further investigation are needed in order to confirm the observed results.…”
Section: Biomass and Seed Yieldsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other hand, it is known that the grain yield strongly varies depending, not only on genotype, but also on site, pedo-climatic conditions, growing season and agronomic practices (Gimplinger et al, 2008;Rivelli et al, 2008). However, the genotypes here investigated, exhibited good potential levels of grain yield in both soil types, reaching values consistent with those reported in literature (Myers, 1996;Kaul et al, 2000;Pospiŝil et al, 2006;Gimplinger et al, 2008;Rivelli et al, 2008;Casini and La Rocca, 2014), even if further investigation are needed in order to confirm the observed results.…”
Section: Biomass and Seed Yieldsupporting
confidence: 80%
“…This genotype showed also a higher harvest index than A. cruentus genotype (0.28 and 0.26, as mean value over the soil type). Casini and La Rocca (2014), in a two-year field experiment carried out in central Italy (Arezzo, Tuscany) compared different genotypes of A. hypochondriacus and A. cruents. They found that A. cruentus exhibited the best growth in the tested environment in comparison to A. hypochondriacus.…”
Section: Biomass and Seed Yieldmentioning
confidence: 99%
“…Amaranth is grown as a leafy vegetable in Nigeria [30]. Additionally, recent research in Italy has confirmed that the country possesses conditions that A. hypochondriacus derivatives find suitable for cultivation [31]. While specialized research is being carried out around cultivation patterns to obtain optimal results in the Russian republic Dagestan [32].…”
Section: Amaranth Cultivation Around the World: A Brief Historymentioning
confidence: 99%
“…recently, a number of studies have been executed to determine the adaptability of amaranth in italy primarily centered on the areas of Central and southern italy. first experiments have been performed to test the adaptation of amaranth plants, and qualitatively evaluate the grain (Massantini et al, 1987;ercoli et al, 1987;alba et al, 1997;Lovelli et al, 2005;rivelli et al, 2008;Casini and La rocca, 2014;Pulvento et al, 2015;el Gendy et al, 2018). The results of these tests highlighted an improved adaptability of A. cruentus, with a spring sowing, for seed production purposes.…”
Section: Introductionmentioning
confidence: 99%
“…not all aspects of the agronomic techniques have been addressed. even if precise indications relating to the sowing density were obtained for A. cruentus (Casini and La rocca, 2014), there is uncertainty with regard to the best sowing period, which is particularly important for a spring-summer crop.…”
Section: Introductionmentioning
confidence: 99%